2020
DOI: 10.1097/ta.0000000000002618
|View full text |Cite
|
Sign up to set email alerts
|

Extraperitoneal packing in unstable blunt pelvic trauma: A single-center study

Abstract: BACKGROUND Hemodynamically unstable pelvic fractures often require a multi-modal approach including both operative and endovascular management. While an important adjunct in hemorrhage control, time to angioembolization even at the most advanced trauma centers may take hours. Extraperitoneal packing (EPP) is a fast and effective procedure that can immediately address pelvic hemorrhage from the retroperitoneal space in severe pelvic injuries. The aim of this study was to evaluate the efficacy of ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 20 publications
0
40
0
3
Order By: Relevance
“…Moreover, the evidence was limited to observational studies. In all studies, the clinical indication to REBOA was haemorrhage from a pelvic fracture or abdominal injury, conditions that recognize optimal clinical results with standard damage control approaches, such as abdominal or extraperitoneal packing [ 38 ] . Both manoeuvres improve haemodynamics and survival and are easily performed by surgical personnel with specific experience.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the evidence was limited to observational studies. In all studies, the clinical indication to REBOA was haemorrhage from a pelvic fracture or abdominal injury, conditions that recognize optimal clinical results with standard damage control approaches, such as abdominal or extraperitoneal packing [ 38 ] . Both manoeuvres improve haemodynamics and survival and are easily performed by surgical personnel with specific experience.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 17 , 18 , 21 – 23 , 25 , 27 , 31 Two of these studies reported more than 80% of patients treated with PPP in their cohort required secondary AE. 23 , 29…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] Injury Severity Score Data were pooled from 16 studies of 516 patients. 11,[15][16][17][18][20][21][22][23][24][25][27][28][29][30]32 The mean ISS in the PPP group was 41 (95% CI, 37-46; n = 384), while, in the AE group, the mean ISS was 36 (95% CI, 33-40; n = 132) (Fig. 5).…”
Section: Agementioning
confidence: 99%
“…In addition, a pelvic orthotic device has been developed and marketed that can be conveniently used in various emergency centres for patients with unstable pelvic fractures (T-POD, Morrisville, NC, US) 11 . Although various studies on the application of PPP and PA in such patients have been published recently, limited studies have compared PEF and PB 8 , 12 – 14 . Therefore, this study aimed to compare clinical outcomes between patients who underwent PEF and PB for pelvic volume reduction.…”
Section: Introductionmentioning
confidence: 99%